A heterotrimeric G protein (Gsα) biomarker may predict antidepressant response in subjects with major depressive disorder - Targum, Steven D.; Gunay, Aksu; Leow, Alex; Ajilore, Olusola A.; Rapaport, Mark H.; Rasenick, Mark M. (Frontiers in Psychiatry, 2025)
BackgroundThe disproportionate sequestration of the heterotrimeric G protein (Gsα) in lipid raft regions during acute depressive episodes can impair neurotransmitter signaling by restricting its interaction with and activation of adenylate cyclase and consequently reduce cyclic adenosine monophosphate (cAMP) production. In humans, Gsα is measured as a peripheral biomarker from platelet samples by using prostaglandin-1 (PGE-1) to stimulate adenylyl cyclase. In two previous studies, Gsα biomarker responses were significantly lower in acutely depressed subjects with major depressive disorder (MDD) than healthy controls and were correlated with the magnitude of symptom severity.MethodsThe potential utility of Gsα biomarker responses to anticipate antidepressant treatment (ADT) response was assessed in 19 acutely depressed MDD subjects receiving ADT for 6 weeks.ResultsFollowing 6 weeks of ADT, Gsα biomarker responses increased significantly in 11 ADT responders compared with 8 non-responders (Mann–Whitney U test; p= 0.033), particularly in subjects with the lowest Gsα biomarker values at screen. All five MDD subjects with Gsα biomarker screen values<1.5 nM cAMP/well became ADT responders with mean Gsα biomarker responses increasing >100% at 6 weeks in contrast to 10% in subjects with higher screen values (p= 0.012).ConclusionADT facilitates translocation of Gsα from the lipid raft region, particularly in MDD subjects who respond to ADT. The findings from this small hypothesis-generating study suggest that the Gsα biomarker assay has potential clinical utility to predict ADT response in depressed subjects with low baseline biomarker values. However, these are exploratory findings that must be replicated in larger studies.